5t+(t+15)-3(t+2)=0

Simple and best practice solution for 5t+(t+15)-3(t+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t+(t+15)-3(t+2)=0 equation:


Simplifying
5t + (t + 15) + -3(t + 2) = 0

Reorder the terms:
5t + (15 + t) + -3(t + 2) = 0

Remove parenthesis around (15 + t)
5t + 15 + t + -3(t + 2) = 0

Reorder the terms:
5t + 15 + t + -3(2 + t) = 0
5t + 15 + t + (2 * -3 + t * -3) = 0
5t + 15 + t + (-6 + -3t) = 0

Reorder the terms:
15 + -6 + 5t + t + -3t = 0

Combine like terms: 15 + -6 = 9
9 + 5t + t + -3t = 0

Combine like terms: 5t + t = 6t
9 + 6t + -3t = 0

Combine like terms: 6t + -3t = 3t
9 + 3t = 0

Solving
9 + 3t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 3t = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 3t = 0 + -9
3t = 0 + -9

Combine like terms: 0 + -9 = -9
3t = -9

Divide each side by '3'.
t = -3

Simplifying
t = -3

See similar equations:

| 3(t+1)=-9 | | 3(-7x+9)=-162 | | -8+62=-2x-112 | | f(x)=logx | | 2.2/4=1 | | 2x^2=2x+2 | | -2(x+7)+4x=4(x-9) | | a-7=3a+1 | | 96=2n-5(2n-8) | | 3(8y-2)=3(4+2y) | | x^3=12x-5x^2 | | c=4c-12 | | x^2+2.5x+1.5=0 | | -80x^2+320-10=0 | | 18d^2+27d+4=0 | | 80-3x=10-10x | | 12-5x/4=1 | | 12=7-y | | 12=7-9 | | 3x+10=-44-6 | | 7f(f+1)= | | 19/x=12 | | 44-10y=10 | | (2x)+2=6 | | -x-8=-2x+0 | | 6+4x=9+x | | 13.28-2.9m=-17.54-7.5m | | 12+2g=24 | | 4r-22r=22 | | -16.85-5.2g=-13.7g+18.43+16.9g | | 7x-15=-41 | | 1+18v=19+19v |

Equations solver categories